Commnunity Perception of Katikuwai Village and Praing Kareha Village Toward Ecotourism Development in Matalawa National Park, NTT - Mangngi Tiga, Melvi Reimon; Putri, Eka Intan Kumala; Ekayani, Meti (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2019)
The Laiwangi Wanggameti area is one of the areas in Matalawa National Park in East Sumba Regency, East Nusa Tenggara Province which has the potential of natural resources that are feasible to be developed as an ecotourism area. The development of Matalawa National Park as an ecotourism area is an alternative to minimize the degradation of the area in the future. The purpose of this study was to analyze the level of rural community dependence on the Laiwangi Wanggameti forest area, analyze the perception of rural communities on ecotourism development and analyze the type of work that the community wants in the natural tourism business. The entire data was obtained through surveys and questionnaires. Qualitative descriptive analysis was used to analyze the overall research objectives. The results showed that the level of dependence of the village community on the Laiwangi Wanggameti forest area was at a high level. The community also has a positive perception of ecotourism development where the community strongly agrees with the development of ecotourism. Meanwhile there are six types of work that people want in business in the field of natural tourism, namely as guides, souvenir service providers, food and drink providers, tourism cooperative managers, parking services and as security guards.